2003
DOI: 10.1563/1548-1336(2003)029<0263:bdiioi>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Bone Density: Its Influence on Implant Stability After Uncovering

Abstract: Primary implant stability and bone density are variables that have long been considered to be essential to achieving predictable osseointegration and long-term clinical survival. Although the dentist can control most factors associated with implant survival, bone density is the one factor that cannot be controlled. Measuring implant stability would assist in determining if an implant has integrated and is ready for the fabrication of the final prosthesis. Changes in implant stability in each type of Bone Quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…The investigators found mean PTVs at second-stage surgery of À 3.82 AE 3.04 for type 1, À 3.7 AE 3.06 for type 2, À 3.3 AE 3.2 for type 3 and À 1.29 AE 3.57 for type 4 quality bone. Another group correlated the same techniques and their results show a different change of PTVs over time in densities 1 and 2 compared with 3 and 4, which could indicate a better bone-to-implant contact over time in better bone densities (Morris et al 2003). A similar finding was published in Truhlar et al (2000); these authors added that hydroxyapathite-coated implants became less stable over time in contrast with noncoated implants, which showed an improvement in stability over time.…”
Section: Relation Of Primary Stability With Bone Densitymentioning
confidence: 67%
“…The investigators found mean PTVs at second-stage surgery of À 3.82 AE 3.04 for type 1, À 3.7 AE 3.06 for type 2, À 3.3 AE 3.2 for type 3 and À 1.29 AE 3.57 for type 4 quality bone. Another group correlated the same techniques and their results show a different change of PTVs over time in densities 1 and 2 compared with 3 and 4, which could indicate a better bone-to-implant contact over time in better bone densities (Morris et al 2003). A similar finding was published in Truhlar et al (2000); these authors added that hydroxyapathite-coated implants became less stable over time in contrast with noncoated implants, which showed an improvement in stability over time.…”
Section: Relation Of Primary Stability With Bone Densitymentioning
confidence: 67%
“…These have been described as being useful methods to assess primary implant stability (Göransson & Wennerberg 2005). They were also reported to yield valuable information on bone healing during osseointegration (Huang et al 2005) and on changes in the bone-implant interface after uncovering (Morris et al 2003).…”
Section: Measurement Of Implant Stabilitymentioning
confidence: 99%
“…8 Survival rates are documented to range from 97.1% to 100% based on implants and from 88% to 100% based on superstructures after 1 to 10 years of follow-up. 9 Multiple factors contribute to implant survivalincluding bone quantity and quality, primary stability, number/length/diameter/distribution of implants across the arch, 10 implant surface and geometry, [11][12][13] loading protocol, prosthetic design, occlusal concept, and maintenance of oral hygiene. There is unanimous agreement that primary stability is closely related to bone structure, and that higher rates of implant survival are obtained in the mandible than in the maxilla.…”
Section: Introductionmentioning
confidence: 99%